2006
DOI: 10.1158/1535-7163.mct-05-0515
|View full text |Cite
|
Sign up to set email alerts
|

Suicide cancer gene therapy using pore-forming toxin, streptolysin O

Abstract: We cloned the streptolysin O gene from the Streptococcus pyogenes genome and tested the possibility of using it as an anticancer reagent. Transient transfection of the streptolysin O gene efficiently killed 293T cells after 12 hours of transfection as determined by lactate dehydrogenase release and propidium iodide uptake. No caspase activity was observed and necrosis was prominent during streptolysin O-induced cell death. Biochemical analysis of streptolysin O protein revealed that the deletion of only 5 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 41 publications
0
39
0
1
Order By: Relevance
“…Similar observations were made for streptolysin O gene transfer, where intracellular toxin expression leads to perforation of cell membranes verified by LDH release. 16 We also showed that intracellularly accumulated CPE causes membrane disruption associated with LDH relase in HCT116 and MCF-7 cells (Figure 4). More interestingly, we detected released biologically active CPE in the medium of transfected cells, although no signal peptide sequence was attached to CPE.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Similar observations were made for streptolysin O gene transfer, where intracellular toxin expression leads to perforation of cell membranes verified by LDH release. 16 We also showed that intracellularly accumulated CPE causes membrane disruption associated with LDH relase in HCT116 and MCF-7 cells (Figure 4). More interestingly, we detected released biologically active CPE in the medium of transfected cells, although no signal peptide sequence was attached to CPE.…”
Section: Discussionmentioning
confidence: 69%
“…Comparable effects were described for streptolysin O-transfected cells. 16 Only in HCT116 cells, delayed (48 h post transfection) release of capases 3 and 7 was detected. This can be attributed to the late action of liberated CPE on non-transfected HCT116 cells in a bystander effect.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations